The interplay of personality traits, anxiety, and depression in Chinese college students: a network analysis - Yang, Tianqi; Guo, Zhihua; Zhu, Xia; Liu, Xufeng; Guo, Yaning (Frontiers in Public Health, 2023)
Background: Anxiety and depression are among the greatest contributors to the global burden of disease. The close associations of personality traits with anxiety and depression has been widely described. However, the common practice of sum scores in previous study limits understanding of the fine-grained connections between different personality traits and anxiety and depression symptoms, and can not explore and compare the risk or protective effects of personality traits on anxiety and depression symptoms. Objective: We aimed to determine the fine-grained connections between different personality traits and anxiety and depression symptoms and to identify the detrimental or protective effects of different personality traits on anxiety and depression symptoms. Methods: A total of 536 college students from China were recruited online, the average age was 19.98 ± 1.11. The Chinese version of the Ten-Item Personality Inventory, Generalized Anxiety Disorder-7 and Patient Health Questionnaire-9 were used to investigate the personality traits and symptoms of anxiety and depression of participants after they understood the purpose and filling method of the survey and signed the informed consents. The demographic characteristics were summarized and the scale scores were calculated. The network model of personality traits and symptoms of anxiety and depression was constructed, and bridge expected influence (BEI) was measured to evaluate the effect of personality traits on anxiety and depression. The edge accuracy and BEI stability were estimated and the BEI difference and the edge weight difference were tested. Results: In the network, 29 edges (indicating partial correlations between variables) bridged the personality community and the anxiety and depression community, among which the strongest correlations were extraversion-fatigue, agreeableness-suicidal ideation, conscientiousness-uncontrollable worry, neuroticism-excessive worry, neuroticism-irritability and openness-feelings of worthlessness. Neuroticism had the highest positive BEI value (0.32), and agreeableness had the highest negative BEI value (-0.27), and the BEI values of neuroticism and agreeableness were significantly different from those of most other nodes (P<0.05).